Cyclic behavior of in-situ exterior beam-column subassemblies with cold joint in column. (1st February 2017) - Roy, Biswajit; Laskar, Aminul Islam
Highlights: Beam-column subassemblies with construction joint in column was tested under cyclic loading. Flexural strength ratios of the specimens were 1.2, 1.4, 1.7 and 2.0. Performance of specimens with construction joint in column under cyclic loading was compared with monolithic specimens. Significant reduction in performance was observed in specimens with construction joint in column. Abstract: Four sets of exterior-beam-column subassemblies with and without construction joint (cold joint) in column to simulate multistage casting at site were tested under cyclic loading. Flexural strength ratios of the specimens were 1.2, 1.4, 1.7 and 2.0. It was observed that the reduction in energy dissipation capacity of the specimens with cold joint were 24–49% compared to control specimens. It was also found that there was 22–36% decrease in ductility of the specimens with cold joint. Reduction in initial stiffness of the specimens with cold joint in column was found to be significant. Difference of peak loads between control and the corresponding specimens with cold joint were negligible. Four sets of reinforced concrete beam specimens with and without cold joint with different percentage of tension reinforcement were tested for flexural capacities under static load. Reduction in peak load of beam specimens with cold joint in comparison to control specimens was found to be insignificant.